Modern lusts : Ernest Borneman - Siegfried, Detlef (Berghahn Books, 2020)
As a jazz musician, filmmaker, anthropologist, sexologist, and crime novelist, the boundlessly curious German autodidact Ernest Borneman exemplified the conflicting cultural and intellectual currents of the twentieth century. In this long-awaited English translation, acclaimed historian Detlef Siegfried chronicles Borneman's journey from a young Jewish Communist in Nazi Berlin to his emergence as a celebrated (and reliably controversial) transatlantic polymath. Through an innovative structure organized around the human senses, this biography memorably portrays a figure whose far-flung obsessions comprised a microcosm of postwar intellectual life.